THE CHANGES OF REGULATION PERTAINING AIRCRAFT IN INDONESIA: BEFORE AND AFTER 9/11 CASE: A LEGAL STUDY VIEWED FROM A 9/11 CASE - Widarto, Bambang (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2024)
An aircraft hijacking as one of crimes in the field of aviation has been recognized as an international crime. The crime more often involved multiple numbers of state’s jurisdictions, both the place of occurrence, its consequences, and the motives of the crime itself. The motive and goal of the crime can or cannot be driven by a politically reason. Initially, many thoughts that one of the characteristics of this crime was taking hostage of people onboard, either flight crew or passengers. However, in the 9/11 case, we can see that perpetrators did not take any people as hostage in an airplane but grabbed a flight control from the pilot in command and used the plane as an air to ground weapon to target civilian objects on the ground. In accordance with the Indonesian Code of Penal Number 1 issued in 2023 under article 579 (1) criminalized a person for committing as air piracy, any person who seizes or maintains the seizure or unlawfully controls an airplane in flight. This article is based on prior normative research, utilizing both secondary data, secondary data consisted of primary and secondary sources were obtained from relevant literature and international and national law. This means that even the newest Law Number 1 of 2023 still requires an element of piracy in the air and an element of an airplane in flight. It is more adequate if the regulations in Indonesia new Criminal Code adopts the provisions of the 2010 Beijing Protocol which has no longer used the element of ‘onboard’ and also modifies the word ‘in flight’ to ‘in service’.